Polarization Bremsstrahlung by Relativistic Electrons in Backscattering Geometry for Diagnosing Atomic Structure of Polycrystals; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Alekseev V. I.; Eliseev A. N.; Irribarra E. F.; Kishin I. A.; Kubankin A. S. Aleksandr Sergeevich; Levina V. S.; Nikulin I. S.; Nazhmudinov R. M.; Sergienko V. I. (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen